HACKER SEBAGAI AKTOR NON-NEGARA - Yusep Ginanjar (Universitas Jenderal Ahmad Yani, 2019)
In 2013 it was revealed that wiretapping had been done by Australian intelligence towards a number of high-ranking officials in Indonesia. This invited the reaction of Indonesian hackers to destroy thousands of important sites in Australia and it is getting a reply from Australian hackers. Of course this is a bad precedent for Indonesia's relationship with Australia. Since its presence in international politics, hackers have been considered non-state actors. This research uses a qualitative method with a phenomenological approach. The purpose of this study is to describe the phenomenon of cyber warfare carried out by both parties as an attempt to attack and maintain the country's sovereignty over their respective versions. The conclusion in this study is the mirror of this cyber war case that hackers are included as non-national actors for their contribution in international politics.